2017
DOI: 10.5805/sfti.2017.19.3.289
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Clothes Sales Forecast System using Weather Information: Focused on S/S Clothes

Abstract: : This study aims to develop clothing sales forecast system using weather information. As the annual temperature variation affects changes in daily sales of seasonal clothes, sales period can be predicted growth, peak and decline period by changes of temperature. From this perspective, we analyzed the correlation between temperature and sales. Moving average method was applied in order to indicate long-term trend of temperature and sales changes. 7-day moving average temperature at the start/end points of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Because most clothing items are seasonal, we expected warmer temperatures to increase sales of S/S products and decrease sales of F/W products. Most previous studies have demonstrated this relationship (Back et al 2019 ; Han 2021 ; Hong 2019 ; Hong and Lee 2013 ; Hong et al 2012 ; Hwangbo et al 2017 ; Jang and Lee 2002 ; Jang and Lim 2003 ; Kim et al 2017 ; Lee et al 2010 ; Lee et al 2011 ; Lim and Lho 2018 ; Oh et al 2017 ), but temperature changes were found to be insignificant within a certain period. Lim and Lho ( 2018 ) found that sales increase with temperature differences, but the more significant the temperature change to some extent, the less impact they have on sales.…”
Section: Utilization Of Weather Information In Clothing Studiesmentioning
confidence: 83%
See 2 more Smart Citations
“…Because most clothing items are seasonal, we expected warmer temperatures to increase sales of S/S products and decrease sales of F/W products. Most previous studies have demonstrated this relationship (Back et al 2019 ; Han 2021 ; Hong 2019 ; Hong and Lee 2013 ; Hong et al 2012 ; Hwangbo et al 2017 ; Jang and Lee 2002 ; Jang and Lim 2003 ; Kim et al 2017 ; Lee et al 2010 ; Lee et al 2011 ; Lim and Lho 2018 ; Oh et al 2017 ), but temperature changes were found to be insignificant within a certain period. Lim and Lho ( 2018 ) found that sales increase with temperature differences, but the more significant the temperature change to some extent, the less impact they have on sales.…”
Section: Utilization Of Weather Information In Clothing Studiesmentioning
confidence: 83%
“…Few studies mention lags between weather changes and sales (Agnew and Palutikof 1999 ; Arunraj and Ahrens 2016 ), but these studies did not provide empirical results. Instead of daily weather changes and sales, Oh et al ( 2017 ) considered the tendency of temperature change due to the influence of longitudinal weather events such as low pressure and high pressure by averaging the temperature change according to the effect of longitudinal weather events. Oh et al ( 2021 ) studied the effect of anomalous weather on the seasonal clothing market in New York as a place-specific case study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation